KUDUMBASHREE PROGRAMME - SUCCESS MANTRA FOR WOMEN IN KAVASSERY PANCHAYAT - ASWATHY & C. ATHENA (International Journal of Research in Applied, Natural and Social Sciences, 2014)
A new paradigm of Participatory Economics (Kudumbashree Programme) has been found emerging in “God’s own country” Kerala. Kudumbashree covers more than 50 percent of the households in Kerala and gives prime importance for the economic empowerment of the indigent masses, especially the poor women of Kerala. Built around three critical components- micro credit, entrepreneurship and women empowerment, Kudumbashree initiative has today succeeded in addressing the basic needs of the less privileged women. In this background a study was carried out with the twin objectives of understanding the working of Neighbour Hood Groups (NHGs) and identifying the socio-economic status of the respondents. The study revealed that the socio economic status of women in Kavassery Panchayat has certainly improved by means of increase in income and savings, decreased debt and their status in and out of their family circumstatnces.